Game Edukasi Fisika Berbasis Smartphone Android Sebagai Media Pembeajaran Fisika - Wati, Widya; Istiqomah, Heti (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: The purpose of this research and development is to develop mobile game physics based on program construct 2 which is a game designed to stimulate thinking power including increasing concentration and solving problems. This research method is research and development (R and D) based on the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The method of retrieving data in this study is through the results of validation and testing of respondents. The validation results obtained from 5 validators with several aspects of assessment obtained an average of 3.70 with the category "feasible", so that from the results of validations obtained from experts, the educational game developed has better quality so that it is feasible to be implemented . The results of product trials on 30 students at Bandar Lampung Middle School 24 showed an average of 3.89 with the criteria of "very interesting". From the results of the trials of respondents the physics education game is very interesting to use as an enrichment media on temperature material and its changes. Abstrak: Tujuan penelitian dan pengembangan ini yaitu mengembangakan mobile game eduaksi fisika berbasis program construct 2 yang merupakan permainan yang dirancang untuk merangsang daya pikir termasuk meningkatkan konsentrasi dan memecahkan masalah. Metode penelitian ini adalah research and development (R and D) berdasarkan model ADDIE  yang terdiri dari analisis, design, development, implementation, and evaluation. Cara pengambilan data pada penelitian ini yaitu melalui hasil validasi dan uji coba responden. Hasil validasi yang didapat dari 5 validator dengan beberapa aspek penilaian didapatkan hasil rata-rata sebesar 3,70 dengan katagori ”layak”, sehingga dari hasil validasi yang diperoleh dari para ahli, game edukasi yang dikembangkan memiliki kualitas yang lebih baik sehingga layak untuk di implementasikan. Hasil uji coba produk pada 30 peserta didik di SMP 24 Bandar Lampung  didapatkan hasil rata-rata sebesar 3,89 dengan kriteria “sangat menarik”. Dari hasil uji coba responden game edukasi fisika ini sangat menarik digunakan sebagai media pengayaan pada materi suhu dan perubahannya.